2020
DOI: 10.1088/1742-6596/1625/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Particle Swarm Optimization Algorithms in Solving Size, Topology, and Shape Optimization

Abstract: This paper focuses on optimizing truss structures while propose best PSO variants. Truss optimization is one way to make the design efficient. There are three types of optimization, size optimization, shape optimization, and topology optimization. By combining size, shape and topology optimization, we can obtain the most efficient structure. Metaheuristics have the ability to solve this problem. Particle swarm optimization (PSO) is metaheuristic algorithm which is frequently used to solve many optimization pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The recent studies have shown that GA (Dede, Bekirolu, & Ayvaz, 2011), TLBO (Dede, 2014), DE (Vu, 2015), Simulated Annealing (SA) (Millan-Paramo, 2018), Ant Lion Optimizer (ALO) (Salar & Dizangian, 2019), Crow Search Algorithm (CSA) (Javidi, Salajegheh, & Salajegheh, 2019) and Artificial Coronary Circulation System (ACCS) algorithm (Kooshkbaghi & Kaveh, 2020) have been used for optimal dimensioning of plane truss structures with minimum weight. Also, optimization of layout and geometry/shape with topology besides dimensioning was done using GA (Chen, Shui, & Huang, 2017;Neeraja, Kamireddy, Kumar, & Reddy, 2017;Rahami, Kaveh, & Gholipour, 2008), Firefly Algorithm (FA) (Miguel, Lopez, & Miguel, 2013), PSO (Harsono et al, 2020;Mortazavi & Toğan, 2016), JA (Degertekin, Lamberti, & Ugur, 2019). In addition, in recent studies, Total Potential Optimization (S. Ç.…”
Section: Weight Optimization Of Plane Trussesmentioning
confidence: 99%
“…The recent studies have shown that GA (Dede, Bekirolu, & Ayvaz, 2011), TLBO (Dede, 2014), DE (Vu, 2015), Simulated Annealing (SA) (Millan-Paramo, 2018), Ant Lion Optimizer (ALO) (Salar & Dizangian, 2019), Crow Search Algorithm (CSA) (Javidi, Salajegheh, & Salajegheh, 2019) and Artificial Coronary Circulation System (ACCS) algorithm (Kooshkbaghi & Kaveh, 2020) have been used for optimal dimensioning of plane truss structures with minimum weight. Also, optimization of layout and geometry/shape with topology besides dimensioning was done using GA (Chen, Shui, & Huang, 2017;Neeraja, Kamireddy, Kumar, & Reddy, 2017;Rahami, Kaveh, & Gholipour, 2008), Firefly Algorithm (FA) (Miguel, Lopez, & Miguel, 2013), PSO (Harsono et al, 2020;Mortazavi & Toğan, 2016), JA (Degertekin, Lamberti, & Ugur, 2019). In addition, in recent studies, Total Potential Optimization (S. Ç.…”
Section: Weight Optimization Of Plane Trussesmentioning
confidence: 99%